2016
DOI: 10.5539/ijc.v8n3p25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mobile Phase Variation and Purification on Chromatogram View by Using Fruits and Rose Extracts and HPLC Method

Abstract: In this study extracts obtained from fruits of bluebery and cranberry and rose leaves were chromatografied by using mobile phase variation and DAD detector. The chromatograms were evaluated under different mobile phase systems such as isocratic and gradient elutions following purification procedure. The best separation conditions of pigments of anthocyanin in extracts and efficiency of purification procedure were searched by using mobile phases in the elution of isocratic and gradient modes. The chromatogram v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The detection of anthocyanins is often performed by Diode Array Detector (DAD) in mass-spectrometry (both MS and MS/MS) which is often coupled with an electrospray ionization source (ESI) [ 76 ]. These methodologies have shown satisfactory results for identifying and quantifying anthocyanins [ 15 , 40 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , <...…”
Section: Analytical Techniques Including Identification and Quantific...mentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of anthocyanins is often performed by Diode Array Detector (DAD) in mass-spectrometry (both MS and MS/MS) which is often coupled with an electrospray ionization source (ESI) [ 76 ]. These methodologies have shown satisfactory results for identifying and quantifying anthocyanins [ 15 , 40 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , <...…”
Section: Analytical Techniques Including Identification and Quantific...mentioning
confidence: 99%
“…In 2021, Li et al reported a study to assess the efficiency of extraction methods from conventional (solvent and ultrasonic extraction) to enzymatic extraction for anthocyanins and their antioxidant properties following each extraction method [ 134 ]. Several reports [ 83 , 97 , 102 , 104 , 106 , 108 , 109 , 110 , 111 , 112 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ] observed that the quantity of anthocyanins in blueberries varies based on the place, collecting/harvesting season, extraction solvent, extraction method, and method of analysis.…”
Section: Analytical Techniques Including Identification and Quantific...mentioning
confidence: 99%